Base-Pair Substitutions in Avian Sarcoma Virus U5 and U3 Long Terminal Repeat Sequences Alter the Process of DNA Integration In Vitro - Hindmarsh, Patrick (American Society for Microbiology, 2001)
We have described a reconstituted avian sarcoma virus (ASV) concerted DNA integration system with specially designed mini-donor DNA containing a supF transcription unit, a supercoiled plasmid acceptor, purified bacterially expressed ASV integrase (IN), and human high-mobility-group protein I(Y). Integration in this system is dependent upon the mini-donor DNA having IN recognition sequences at both ends and upon both ends of the same donor integrating into the acceptor DNA. The integrated DNA product exhibits all of the features associated with integration of viral DNA in vivo (P. Hindmarsh et al., J. Virol., 73:2994–3003, 1999). Individual integrants are isolated from bacteria containing drug-resistant markers with amber mutations. This system was used to evaluate the importance of sequences in the terminal U5 and U3 long terminal repeats at positions 5 and/or 6, adjacent to the conserved CA dinucleotide. Base-pair substitutions introduced at these positions in U5 result in significant reductions in recovered integrants from bacteria, due to increases in one-ended insertion events. Among the recovered integrants from reactions with mutated U5 but not U3 IN recognition sequences were products that contain large deletions in the acceptor DNA. Base-pair substitutions at positions 5 and 6 in U3 mostly reduce the efficiency of integration of the modified donor. Together, these results indicate that sequences directly 5′ to the conserved CA dinucleotide are very important for the process of concerted DNA integration. Furthermore, IN interacts with U3 and U5 termini differently, and aberrant end-processing events leading to nonconcerted DNA integration are more common in U5 than in U3.